Panic party : a Roger sheringham case - Berkeley, Anthony, 1893-1971 (Society of Authors, 2001)
Mr Pidgeon is the unlikely and lucky owner of a large yacht and a desert island. Gentleman sleuth Roger Sheringham is one of the members of the party Pidgeon invites for a cruise. When the ship and its crew return to port without them, the party are marooned for a fortnight on the private island. Sheringham is shocked to discover Pidgeon has organised the whole thing as an experiment. He has brought them together to enact a bizarre murder and detection game. But then the madness starts and tragedy strikes... AUTHBIO: A journalist as well as a novelist, Anthony Berkeley was a founding member of the Detection Club and one of crime fiction's greatest innovators. He was one of the first to predict the development of the 'psychological' crime novel and he sometimes wrote under the pseudonym of Francis Iles. He wrote twenty-four novels, ten of which feature his amateur detective, Roger Sheringham.